Case Study on the Implementation of Implementation Strategies: Verbal Methods in Patients at Risk of Violent Behavior - Ghani, Farid; Rahmawati, Arni Nur (PROMOTOR, 2024)
Mental health issues of concern in Indonesia are severe mental disorders, including schizophrenia, which have a significant impact on patients and society. This study aims to evaluate the effectiveness of the implementation of the Implementation Strategy (SP) to control violent behavior by verbal means in managing the risk of violent behavior in patients with mental disorders at Soerojo Hospital. The research method is a descriptive case study with a nursing process approach. Data collection was carried out by means of observational interviews, and patient medical design documentation studies. This research instrument uses a nursing care format. The subjects in this case study are schizophrenic patients at risk of violent behavior at Soerojo Hospital. The results of the study showed that the training to recognize risks and control violent behavior physically, verbally, and spiritually was effectively applied to patients, as seen in Mr. F who successfully controlled violent behavior by following the SP to control violent behavior in a verbal way. The implementation of this strategy reduces the incidence of violent behavior, improves safety, and improves the quality of life of patients. This study also highlights the importance of training and education for health workers as well as the role of family support in managing violent behavior. In conclusion, the implementation of SP I, II, and III at Soerojo Hospital is effective and can be a model in dealing with the risk of violent behavior in patients with mental disorders, so that it is expected to improve the quality of mental health services in Indonesia.